1997
DOI: 10.1007/s001250050700
|View full text |Cite
|
Sign up to set email alerts
|

Defective regulation of triglyceride metabolism by insulin in the liver in NIDDM

Abstract: Features of diabetic dyslipidaemia in non-insulin-dependent diabetes mellitus (NIDDM), such as a low HDL cholesterol concentration, the preponderance of small dense LDL and postprandial fat intolerance are considered to be metabolic consequences of elevated plasma triglycerides [1]. The mechanism underlying hypertriglyceridaemia in NIDDM is still unclear. A majority of studies indicate that the elevation of plasma triglycerides in NIDDM result from an overproduction of VLDL triglyceride [2,3] and apo B [4,5] b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
204
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(220 citation statements)
references
References 45 publications
13
204
0
3
Order By: Relevance
“…Stable isotope tracers have been used in conjunction with compartmental modelling to elucidate the kinetics of apoB (a key structural protein in lipoproteins) and triglyceride across VLDL subfractions simultaneously. Adiels' model [2] has proven to be a particularly useful tool in determining how physiological features impact VLDL size and dyslipidemia [4,3,39,38]. A more in-depth model of VLDL assembly has been proposed by Shorten and Upreti [50] in which the lipid composition of secreted VLDLs can be determined from uptake of individual free fatty acids after elongation and desaturation by liver enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotope tracers have been used in conjunction with compartmental modelling to elucidate the kinetics of apoB (a key structural protein in lipoproteins) and triglyceride across VLDL subfractions simultaneously. Adiels' model [2] has proven to be a particularly useful tool in determining how physiological features impact VLDL size and dyslipidemia [4,3,39,38]. A more in-depth model of VLDL assembly has been proposed by Shorten and Upreti [50] in which the lipid composition of secreted VLDLs can be determined from uptake of individual free fatty acids after elongation and desaturation by liver enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of the effect of hyperinsulinaemia on VLDL-TAG secretion in type 2 diabetes have been inconsistent with reports showing impaired [11,12] or preserved [7] suppression. This may be attributed to the prolonged and supraphysiological exposure to insulin during hyperinsulinaemic clamps, which may override the impaired suppression in type 2 diabetes at more physiological insulin concentrations.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, acute hyperinsulinaemia leads to a rapid inhibition of hepatic VLDL-TAG secretion, as evidenced from data stemming from in vitro studies, animal models and human studies [6][7][8]10]. Some previous studies have shown that diabetic patients fail to downregulate secretion of large VLDL (VLDL 1 ) in an experimental setting with high-dose insulin infusion [11,12], whereas we reported a preserved suppressive effect of hyperinsulinaemia on VLDL-TAG secretion [7]. The impact of meal-induced hyperinsulinaemia, on the other hand, is less well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The major lipoprotein abnormality in Type 2 diabetes is increased VLDL synthesis, in part due to the hepatic recirculation of NEFA outflowing in excess from adipose tissue, and in part as a result of de novo synthesis in the presence of hyperglycaemia and hyperinsulinaemia. This occurs because the hepatic VLDL synthesis, usually suppressed by insulin, continues unabated in the condition of insulin resistance [70]. There is also an impediment in VLDL and chylomicron removal due to lower than normal lipoprotein lipase (LPL) activity in adipose tissue in diabetes [71,72,73].…”
Section: Diabetes Complications: Atherosclerosis and Hyperlipidaemiamentioning
confidence: 99%